THE INFLUENCE OF LIFESTYLE, HALAL LABEL, AND PRICE PERCEPTION ON THE PURCHASE DECISION OF WARDAH LIPSTICK - Dista Aferonika; Mulyo Budi Setiawan (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2022)
This study aims to analyze the effect of lifestyle, halal label and price perception on the purchasing decision of Wardah cosmetics in the lipstick category in Semarang City. The data used is sourced from a questionnaire in the form of a google form link (primary data). The sampling method used non-probability sampling method. The results showed that lifestyle and price perception had a positive effect on purchasing decisions, while the halal label had no effect on purchasing decisions. The higher the lifestyle, the higher the purchasing decision for Wardah lipstick. This study resulted in 55.9% of purchase decision variables can be explained by lifestyle, halal label and price perception, while 44.1% is influenced by other variables outside the study.